Informing patients on planned consultation time – a randomised controlled intervention study of consultation time in primary care - Oskar Lindfors; Sara Holmberg; Mattias Rööst (Scandinavian Journal of Primary Health Care, 2019)
Objective: To investigate whether patients’ pre-consultation knowledge of the time frames for the consultation influences the actual consultation time and/or patient and physician related outcomes; satisfaction and enablement. Design: Randomised controlled blinded intervention study. Setting: Four strategically chosen Primary Health Care Centres (PHCC:s) in Kronoberg county in Sweden participated. Intervention: Pre-consultation information on planned consultation time. During one week in each PHCC consecutive patients were randomised to intervention group or control group, when booking an appointment with a physician. Subjects: Patients >18 years of age. Main outcome measures: Consultation time, patient satisfaction, patient enablement and physician satisfaction. Results: No significant difference in consultation time was found between the intervention group and control group. No differences were seen between intervention group and control group regarding any of the other measures. Stratified data showed significantly shorter consultation time for the intervention group in one of the PHCC:s and for employed physicians. Employed physicians also rated consultations as being easier and were more satisfied with their consultations compared to non-employed physicians. Conclusion: Information on the planned consultation time has a potential to decrease consultation time in certain settings. No negative side effects were found in this study. Key points Patients prepare before their consultation but to influence its contents and length is difficult. Informing patients on estimated consultation time can influence actual consultation time. Informing patients on planned consultation time has no adverse effects in this study.